The Novel Coronavirus 2019 (COVID-19): A Narrative Review - Rezapour Baratali; Jalil Musavi Sayed; Shirzadeh Maleki Faezeh (International Journal of Coronaviruses, 2020)
One of the key steps in determining how to prevent the viral disease is to identify the virus. The virus lives in different ways and in different environments. It lives in the air, in the sea, on plants, animals and objects and humans. Some people put humans on the path of developing zoonotic diseases that are specific to animals but also involve people with unhealthy behaviors. In the food chain, each animal is hunted by other animals and feeds on other animals or plants and other objects. Bacteriophages are viruses that kill bacteria. And there are creatures that kill viruses and this is the biological struggle with viruses. When the virus enters the body, it performs a series of activities that lead to a series of symptoms in the patient. These symptoms include the behavior of viruses. These are among the ecological and behavioral characteristics of viruses that need to be fully understood in order to limit viruses and deal with epidemics and pandemics. In this study, we try to reach a conclusion by reviewing the articles that have information about the behavioral (signs and symptoms) and ecological characteristics of viruses and use these findings in order to combat viruses.
Keywords: COVID-19